Obama's Surge: A Bureaucratic Politics Analysis of the Decision to Order a Troop Surge in the Afghanistan War. Issue 3 (4th February 2013) - Marsh, Kevin
Abstract : This study examines the decision‐making process leading to President Barack Obama's decision to order a troop surge in Afghanistan in December 2009. I analyze the decision‐making process according to the precepts of the bureaucratic politics model and conclude that the bureaucratic politics model provides a compelling and descriptively accurate account of the Afghanistan surge decision‐making process. Actors' policy preferences were influenced by consideration of bureaucratic role and position within government, significant examples of political activity occurred throughout the strategy review, and the ultimate decision was a political compromise.